Texture reconstruction of 3D sculpture using non-rigid transformation. - Zhang, Fan; Huang, Xianfeng; Fang, Wei; Zhang, Zhichao; Li, Deren; Zhu, Yixuan (Journal of Cultural Heritage, 2015)
Sculptures, one of the most important forms of cultural heritage, exist in numerous temples, towers and grottoes. The current generation of high precision 3D digital sculpture models is a primary reality-based modeling tool for digital documentation, archaeological research, virtual restoration, and digital exhibition. However, high precision texture mapping remains a challenge in high fidelity digital reconstruction of complex sculptures, especially in the areas of rich geometrical details. This paper proposes a method to texture mapping one image onto the sculpture model to deal with the mapping problem problems caused by the image distortion and the model deformation. Firstly, we use a rigid pinhole camera model to project the image onto the geometric model to acquire primary texture mapping, where direct linear transformation is employed to estimate the elements of exterior orientation of the texture image. Then, we propose a non-rigid transformation model, called weighted thin-plate spline (W-TPS), discuss the theoretical derivation and the establishment of the W-TPS function, and apply this model to adjust the primary texture mapping results. The proposed method can precisely project the image onto the geometrical model both globally and locally. We conduct three experiments to verify the efficiency and feasibility of the proposed method using the sculptures in Dunhuang Mogao Grottoes in western China, which was inscribed on World Heritage List by UNESCO in 1987.